Efficient Code Clone Analysis to Detect Vulnerability in Dynamic Web Applications - Vineetha, KR; Santhana Krishna, N (International Journal of Computer Sciences and Engineering, 2025)
In this system an approach to clone analysis and Vulnerability detection for Web applications has been proposed together with a prototype implementation for web pages. Our approach analyzes the page structure, implemented by specific sequences of HTML tags, and the content displayed for both dynamic and static pages. Moreover, for a pair of web pages we also consider the similarity degree of their java source. The similarity degree can be adapted and tuned in a simple way for different web applications. We have reported the results of applying our approach and tool in a case study. The results have confirmed that the lack of analysis and design of the Web application has effect on the duplication of the pages. In particular, these results allowed us to identify some common features for the web pages that could be integrated, by deleting the duplications and code clones. Moreover, the clone analysis and Vulnerability detection of the pages enabled to acquire information to improve the general quality and conceptual/design of the database of the web application. Indeed, we plan to exploit the results of the code clone analysis method to support web application reengineering activities.